Стратегія подолання регіональної диференціації добробуту населення України - Горященко, Ю.Г. (Управління економікою: теорія та практика, 2013)
Проаналізовано проблеми міжрегіональної диференціації доходів населення та рівня життя, зроблено висновок про його надмірний рівень, що не сприяє консолідації українського суспільства. обґрунтовано необхідність у державній стратегії регіонального розвитку, визначено пріоритетне завдання вирівнювання доходів населення, окреслено шляхи його досягнення. Проанализированы проблемы межрегиональной дифференциации доходов населения и уровня жизни, сделан вывод о его чрезмерном уровне, что не способствует консолидации украинского общества. Обоснована необходимость Государственной стратегии регионального развития определить приоритетную задачу выравнивания доходов населения, определены пути его достижения The situation formed in Ukraine is such that the region where a person lives becomes a determining factor, not only in the economic situation, but also in qualitative characteristics of living, in particular the availability of basic social services and ecologically safe environment, opportunities to provide a comprehensive development of children, support their health. Excessive differentiation of incomes of the population in the regions of Ukraine is the result of a considerable gap in the living standards of the communities. In most regions the opportunities of human development are at low level that prevents the accumulation of human capital, which is the main factor of the economic growth. The low level of welfare and its considerable unevenness generate the interregional social contradictions. In conditions, when there is a problem of regional differentiation in Ukraine, the state efforts concerning levelling the welfare could become an instrument of consolidation of the society. The author of the article analyses problems of interregional differentiation of the population’s incomes and standards of living. The conclusion is made that the excessive level of differentiation does not contribute to the consolidation of Ukrainian society. It is necessary to form the state strategy of regional development. The priority task of leveling the incomes of the population is defined and the ways to achieve it are maked.